The Impact of Road Side Friction on the Traffic Flow of Arterial Roads in Varanasi - Srivastava, Kartik; Kumar, Ajay (Engineering, Technology & Applied Science Research, 2023)
Varanasi’s prominence as a cultural and historical center means it receives visitors from all over the world. The city’s tourism industry is a boon to the local economy. Better transportation infrastructure is crucial to attracting more tourists and increasing revenue. Varanasi is currently experiencing terrible difficulties due to various roadside frictional activities. Vehicle ownership grows in tandem with population growth. The increase in the number of vehicles on the road significantly impacts the reliability of the transportation network since land availability is fixed. The various roadside frictional activities usually found in the streets of Varanasi are on-street parking, pedestrian crossing, and Non-Motorized Vehicles (NMVs). There are not enough legal on-street parking and segregated lanes for NMVs/slow-moving vehicles or demarcation for pedestrian movements in the old city of Varanasi. Vehicles in Varanasi are traditionally parked on the street due to the narrow carriageways. Slow-moving vehicles are forced to move with fast-moving vehicles, and pedestrian crossings affect traffic flow. Integrated movement of slow-moving vehicles and rapid-moving vehicles affects traffic speed, pedestrian crossings impact the Level of Service (LOS), and on-street parking results in the reduction of the effective carriageway width and, hence, road capacity. This paper aims to identify the impact of pedestrian crossings, NMVs, and on-street parking on the traffic flow, speed, capacity, and LOS of urban arterial roads in Varanasi. To achieve this objective, two case studies were considered: the base section (with minimum side friction) and the friction section (with maximum side friction). The videography method was used for data collection. Nine hours of data were collected from 9:30 am to 6:30 pm. The video was played on the screen for data extraction. The speed model was developed by using fundamental diagram methods. Speed-density curve was drawn using Greenshield’s model. The speed-flow curve was derived from the speed-density curve to estimate the capacity at the base and friction sections. Reduction in capacity was determined by comparing friction section capacity with base section capacity. V/C ratio of a particular road compared with the V/C value provided by IRC 106 to predict LOS. A correlation model was developed between the percentage reduction in capacity and road width. Increase in parking, the proportion of NMVs, and pedestrian crossing frequency reduce the traffic flow. It was observed that a 6.42% capacity loss occurs at a 7.00% reduction in effective width, and a 35.09% loss occurs at a 36.02% reduction in effective width. Roads with frictional activities found their LOS class affected up to LOS-E (for the Bhelupur section).